Tantangan Pemberian Bantuan Luar Negeri Indonesia ke Pasifik Berdasarkan Model Birokrasi Politik - Andi Sintia (Lembaga Pengembangan Kinerja Dosen, 2024)
This article explains the challenges faced by Indonesia in providing foreign aid to the Pacific region. The background of the research shows that Indonesia has a strong commitment to contribute to sustainable development in Pacific countries, but the implementation of aid programmes still faces various obstacles, such as a lack of inter-agency coordination and a non-integrated approach. The purpose of this research is to analyse the effectiveness of Indonesia's foreign aid policy using the Political Bureaucracy Model. The method used is a descriptive qualitative approach, which involves literature review and in-depth interviews with relevant stakeholders. The results found that the main challenges include clarity of objectives, lack of strategic approach, and limited funding. It can be concluded that there is a need to develop a long-term strategy and improve inter-agency coordination to optimise the implementation of foreign aid programs, so that Indonesia can be more effective in achieving national goals and supporting Pacific countries.